2020
DOI: 10.1186/s13362-020-00086-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of flame cutting for steel plates with solid phases and melting

Abstract: The goal of this work is to describe in detail a quasi-stationary state model which can be used to deeply understand the distribution of the heat in a steel plate and the changes in the solid phases of the steel and into liquid phase during the flame cutting process. We use a 3D-model similar to previous works from Thiébaud (J. Mater. Process. Technol. 214(2):304-310, 2014) and expand it to consider phases changes, in particular, austenite formation and melting of material. Experimental data is used to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The torch angle was changed for the fourth cut to 45°, the preheating period was 60 seconds, and the cutting speed was 140 mm/min. The block's edge wall was melted by the cutting heat because the torch was too close to the edge (distance =15mm) [14,15].…”
Section: Specimen 1 Cutting Testmentioning
confidence: 99%
“…The torch angle was changed for the fourth cut to 45°, the preheating period was 60 seconds, and the cutting speed was 140 mm/min. The block's edge wall was melted by the cutting heat because the torch was too close to the edge (distance =15mm) [14,15].…”
Section: Specimen 1 Cutting Testmentioning
confidence: 99%
“…Then oxygen from the torch blows the melted steel away. Many studies have concluded that the heat source is uniformly distributed within a volume that resembles a cylinder with a truncated cone at both ends [8]. To indicate the direction of cutting heat source movement, the model can be split into two parts like the Goldak heat source model, as shown in Figure 1.…”
Section: Heat Source For Welding and Cutting Simulationmentioning
confidence: 99%
“…Despite the widespread use of the given technologies in practice, real results on the thermal cycling during thermal cutting are rather sporadic [5][6][7]. When numerical simulations are used to optimize the process, the temperature cycle is the basic dependence to set up and verify the process [8][9][10]. This paper focuses on the two most widely used thermal cutting technologies, namely oxyacetylene flame cutting and air plasma cutting.…”
Section: Introductionmentioning
confidence: 99%